La « social-démocratie » : nouvel horizon politique des années 1960 en Irlande ? - Julien Guillaumond (Revue LISA)
In a context of economic and social changes in the 1950s-60s, two different political projects, a social-democratic project and a corporatist one, were offered to the Irish people for the future of their country. After studying each of these projects in turn, this article tries to understand the reasons why social democracy failed to win over Irish opinion in the 1960s.